PENERAPAN STRATEGI KANVAS UNTUK PERANCANGAN MODEL PEMASARAN PROGRAM STUDI - Mohammad Kurniadi Rasyid; Dyah Purwaningsih (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2022)
The purpose of this research is to find a marketing model for the study program that is in accordance with the steps recommended by the blue ocean shift. The data used in this study were obtained from distributing questionnaires to management study programs from 10 private universities in West Java and Jakarta. The canvas analysis technique of blue ocean shift is used to analyze the marketing activities of each study program that is sampled and determine the conditions of competition between study programs. The results of the study indicate that there are marketing activities that should be reduced by study programs and replace them with other, more innovative activities. Changes in marketing activities will result in a new marketing model of the study program that will attract enthusiasts by avoiding heavy competition from competitors as suggested by the blue ocean strategy.